CAUSES OF PATAU SYNDROME - Farmonova , Rukhshona Farrukhovna; Ergashev, Zafar Bakthtiyorovich; Kholmurodova, Dilafruz (Educational Research in Universal Sciences, 2024)
Clinical symptoms of Patau’s disease were identified in the 17th century. 13th of the disease connection with the increase in the number of paired chromosomes in 1960 K. Patau was identified by, therefore, this disease is associated with the name of this scientist. 13-chromosomal trisomy occurs in approximately 1/10,000 births; about 80% cases are complete trisomy on the 13th chromosome. Mother’s age (average 31 age), the higher the probability of developing this syndrome will be Babies are usually too small for their gestational age. Medium anomalies are frequent and include holoprosencephaly (correct forebrain not splitting), anomalies of the face, for example, clefts of the upper lip and palate, microphthalmia, retinal colobomas (cracks) and retinal dysplasia enters. Brow systems are small, eyes are located far from each other. Ears irregularly shaped and usually located lower. Skull defects and dermal sinuses are also common. Single transverse palmar fold, polydactyly and visible narrow fingernails are common. About 80% in cases, severe congenital anomalies of the cardiovascular system are detected; dextrocardia is common. Genital organs are often atypical in both sexes there is: cryptorchidism in boys, bicornuate uterus in girls. There was PS special complications in pregnancy - this frequency occurs in 50% of PS.